2009
DOI: 10.1136/emj.2008.065508
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester Triage System provides good reliability in an Australian emergency department

Abstract: The MTS is a reliable system of triage in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
0
28
0
10
Order By: Relevance
“…In two other studies, one in Sweden and one in Australia, the MTS showed good reliability between observers, with Kappa indices of 0.80 and 0.81, respectively (15)(16) . The agreement between the MTS and two other protocols for risk classification was also evaluated.…”
Section: VImentioning
confidence: 78%
See 4 more Smart Citations
“…In two other studies, one in Sweden and one in Australia, the MTS showed good reliability between observers, with Kappa indices of 0.80 and 0.81, respectively (15)(16) . The agreement between the MTS and two other protocols for risk classification was also evaluated.…”
Section: VImentioning
confidence: 78%
“…It is noted that of the five identified articles that dealt with the reliability of the MTS, two (40%) were performed in the Netherlands (13)(14) , one (20%) in Brazil (12) , one (20%) in Sweden (15) and one (20%) in Australia (16) . Four (80%) studies were conducted with adults (12,(14)(15)(16) and one (20%) with a pediatric population (13) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations